2017
DOI: 10.1016/j.jmb.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Derepression of SaPIbov1 Is Independent of φNM1 Type 2 dUTPase Activity and Is Inhibited by dUTP and dUMP

Abstract: Staphylococcus aureus is an opportunistic human pathogen able to transfer virulence genes to other cells through the mobilization of S. aureus pathogenicity islands (SaPIs). SaPIs are derepressed and packaged into phage-like transducing particles by helper phages like 80α or φNM1. Phages 80α and φNM1 encode structurally distinct dUTPases, Dut80α (type 1) and DutNM1 (type 2). Both dUTPases can interact with the SaPIbov1 Stl master repressor, leading to derepression and mobilization. That two structurally distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…However, the structural characterization of the ϕDI Dut A73L mutant has shown that this mutation promotes a compact conformation that could be stabilizing the dimer, supporting our proposition. During the review of this manuscript, Dokland and collaborators published that Stl interaction with the dimeric Dut from phage ϕNM1 was inhibited by dUTP in close agreement with our results and proposition [ 24 ]. However, the authors indicate that the product dUMP also has an inhibitory capacity for the Stl-ϕNM1 Dut interaction, in contrast to the results obtained here for two alternative inducing dimeric Duts.…”
Section: Discussionsupporting
confidence: 88%
“…However, the structural characterization of the ϕDI Dut A73L mutant has shown that this mutation promotes a compact conformation that could be stabilizing the dimer, supporting our proposition. During the review of this manuscript, Dokland and collaborators published that Stl interaction with the dimeric Dut from phage ϕNM1 was inhibited by dUTP in close agreement with our results and proposition [ 24 ]. However, the authors indicate that the product dUMP also has an inhibitory capacity for the Stl-ϕNM1 Dut interaction, in contrast to the results obtained here for two alternative inducing dimeric Duts.…”
Section: Discussionsupporting
confidence: 88%
“…Importantly, dimeric and trimeric Duts are completely unrelated both in sequence and structure, representing a nice example of convergent evolution ( Penadés et al, 2013 ). While the 80α and ϕ11 phage-encoded trimeric Duts were initially described as the SaPIbov1 inducers ( Tormo-Más et al, 2010 ; 2013 ), the dimeric Dut from phage ϕNM1 also induces SaPIbov1 ( Hill and Dokland, 2016 ; Hill et al, 2017 ). The fact that both dimeric and trimeric Duts induce SaPIbov1 raised the interesting possibility that the Stl repressors could target different phage proteins, significantly increasing the capacity of the SaPIs to be induced and transferred.…”
Section: Introductionmentioning
confidence: 99%
“…also Supplementary Figure S2). However, we also note here that specific mutation of K159 to alanine did not abolish DUTφNM1:Stl complex formation either in vitro or in vivo, thus this residue is not an essential factor in the protein–protein interaction [15].…”
Section: Resultsmentioning
confidence: 99%
“…In parallel to these studies it has also been revealed that not only the homotrimeric phage dUTPases but a homodimeric dUTPase from φNM1 phage is also capable to interact with the Stl of SaPIbov1 [14,15]. Hill et al provided clear evidence also for the direct interaction of the φNM1 phage dUTPase and Stl [14].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation